2021
DOI: 10.3892/mmr.2021.11902
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulated expression levels of USP46 promote the resistance of ovarian cancer to cisplatin and are regulated by PUM2

Abstract: Ovarian cancer (OC) is a major contributor to cancer-related mortality in women. Despite numerous drugs being available for the treatment and improving the prognosis of OC, resistance to clinical chemotherapy remains a major obstacle for the treatment of advanced OC. Therefore, determining how to reverse the chemoresistance of OC has become a research hotspot in recent years. The present study aimed to reveal the potential mechanism of OC chemoresistance. Reverse transcription-quantitative PCR and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We found that PUM2 exhibited higher activity in ovarian cancer cells (Fig. 2F), and targeting PUM2 has been identi ed as an effective way to reverse cisplatin resistance in OvC 21 . HNRNPDL exhibited higher activity in T cells of lung cancer (Fig.…”
Section: Rbp Regulators Exhibit Cancer and Cell Speci Citymentioning
confidence: 81%
“…We found that PUM2 exhibited higher activity in ovarian cancer cells (Fig. 2F), and targeting PUM2 has been identi ed as an effective way to reverse cisplatin resistance in OvC 21 . HNRNPDL exhibited higher activity in T cells of lung cancer (Fig.…”
Section: Rbp Regulators Exhibit Cancer and Cell Speci Citymentioning
confidence: 81%
“…PUM2 exhibited higher activity in ovarian cancer cells (Fig. 2f ), and targeting PUM2 has been identified as an effective way to reverse cisplatin resistance in OvC 23 . HNRNPDL exhibited higher activity in T cells of lung cancer (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Map2k6 played an important role in modulating I/R-induced neuron cell apoptosis [ 27 ]. PUM2 was validated to be involved in the development of ovarian cancer [ 10 ], acute ischemic kidney injury [ 11 ] and mature neurons [ 12 ]. Nonetheless, whether PUM2 is involved in cerebral I/R injury still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…PUM2 is a member of the PUM family, which has been reported to participate in the progression of several diseases. For instance, PUM2 modulates the resistance to cisplatin in ovarian cancer via regulating USP46 expression [ 10 ]. PUM2 governs mitochondrial quality in acute ischemic kidney injury through cooperating with Mff [ 11 ].…”
Section: Introductionmentioning
confidence: 99%